Multi-biomarker mortality prediction in patients with aortic stenosis undergoing valve replacement. Issue 2 (August 2020) - Spampinato, Ricardo A.; Bochen, Rafal; Sieg, Franz; Weiss, Stefan; Kornej, Jelena; Haunschild, Josephina; von Aspern, Konstantin; Strotdrees, Elfriede; Noack, Thilo; Lehmann, Sven; Etz, Christian; Borger, Michael A.
Highlights: Association of biomarkers showed mortality prediction after aortic valve replacement. Patients with three elevated biomarkers had a >4-fold increased risk of death. EuroScore had a lower prediction profile than a multi-biomarker approach. Combination of EuroScore with three biomarkers showed a progressive risk of death. Abstract: Objectives: The prognostic value of biomarkers in aortic stenosis (AS) remains understudied. We investigated whether a combination of biomarkers related to cardiovascular stress, inflammation, and damage is associated with mortality in patients with severe AS undergoing surgical aortic valve replacement (SAVR). Methods: From a prospective registry of patients with severe AS referred for SAVR, 499 participants (mean age, 68 ± 8.5 years; 292 male) with available preoperative echocardiograms and biomarker data were included. Preoperative concentrations of NT-pro-B-type natriuretic peptide, high-sensitivity cardiac troponin T, and C-reactive protein were dichotomized as high or low, according to calculated cut-off values. Results: The mean follow-up time was 775 ± 410 days; 25 patients died. Only patients with elevated levels of all three biomarkers (n = 55) showed increased mortality [hazard ratio (HR), 7.26; 95% confidence interval (CI), 2.52–20.93; p < 0.001; reference group, no elevated biomarkers, n = 159]. Patients with elevated levels of the three biomarkers had higher 3-year all-cause mortality (24% vs. 4.5%); this remained true after multivariable adjustment (HR, 4.08; 95% CI, 1.87–8.87; p < 0.001). Patients with EuroSCOREs (logES) >3.0% tended to exhibit a higher risk of all-cause mortality (HR, 2.19; 95% CI, 0.98–4.87; p = 0.055); the mortality rate was 12-fold higher when logES >3 was combined with the three elevated biomarkers. This combination also showed a net reclassification improvement of 33% and significant likelihood-ratio test results. Conclusions: A multiple biomarker approach might be useful for predicting postoperative mid-term mortality in patients with severe AS undergoing SAVR. Further large-scale prospective validation should be performed.